2011
DOI: 10.1007/s11325-011-0616-8
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality and asthma control and quality of life in non-severe and severe asthma

Abstract: Purpose The effect of sleep quality on asthma control independent from common comorbidities like gastroesophageal reflux disease (GERD) and obstructive sleep apnea (OSA) is unknown. This study examined the association between sleep quality and asthma control and quality of life after accounting for OSA and GERD in non-severe (NSA) and severe (SA) asthma. Methods Cross-sectional data from 60 normal controls, 143 with NSA, and 79 with SA participating in the Severe Asthma Research Program was examined. Those w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
100
2
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(120 citation statements)
references
References 28 publications
11
100
2
4
Order By: Relevance
“…It has been documented that parental marital conflicts (22), low socioeconomic status (23), household second-hand smoke or prenatal tobacco exposure (24), and preterm birth are related to ADHD or ODD. However, two limitations of this study deserve discussion.…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented that parental marital conflicts (22), low socioeconomic status (23), household second-hand smoke or prenatal tobacco exposure (24), and preterm birth are related to ADHD or ODD. However, two limitations of this study deserve discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that sleep difficulties persist even in those without asthma-related nocturnal awakenings, with 20% to 46% reporting moderate to severe difficulty staying asleep. 7,10,12 These data suggest that poor sleep may not solely be due to nighttime asthma awakenings, but may represent comorbid insomnia. Insomnia disorder is characterized by selfreported difficulty falling asleep, staying asleep, or poor quality sleep and accompanying daytime symptoms such as fatigue, irritability, and impaired concentration.…”
mentioning
confidence: 93%
“…[7][8][9][10][11][12] Sleep difficulties are often considered a consequence of nocturnal awakenings resulting from nighttime asthma symptoms and/or the need for rescue inhaler medication, which will resolve with adequate control of asthma symptoms. Previous studies suggest that sleep difficulties persist even in those without asthma-related nocturnal awakenings, with 20% to 46% reporting moderate to severe difficulty staying asleep.…”
mentioning
confidence: 99%
“…Recent studies reported that, asthma is more difficult to control in the obese patient [41][42][43], since different type of airway inflammation, obesity related comorbidities such as obstructive sleep apnea [2]. Luyster and his colleagues showed that, poor sleep quality is associated with poor asthma control and quality of life among asthmatics [44]. Similar to Luyster's result, in our study we found that there was negative correlation between ACT and PSQI (r=-0,620; p<0.001).…”
Section: Resultsmentioning
confidence: 99%